2017
DOI: 10.1002/joc.5024
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between wintertime extreme temperature events north of 60°N and large‐scale atmospheric circulations

Abstract: The increased extreme warm and decreased extreme cold temperature events across the Arctic strongly influence the natural environment as well as the societal activities. This study investigates temporal and spatial variability of wintertime extreme high and low temperature events defined by the 95 and 5% percentiles across the Arctic and subarctic regions, respectively (north of 60°N) using data from 238 stations in the Global Summary of the Day for the period 1979–2016. Empirical orthogonal function analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Guan et al (2015), examining daily minimum and maximum temperature, found that the Yangtze River Basin was dominated by a general cooling trend during the period 1960-1985, but a warming trend in 1986-2012 and that cold-related indices significantly decreased and warm-related indices significantly increased. The increased extreme warm temperature and decreased extreme cold temperature events at a regional scale strongly influence the natural environment (Overland et al, 2014;Yu et al, 2017). Therefore, a quantitative analysis and prediction of the trends and changes of extreme temperature in local scale is highly required.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al (2015), examining daily minimum and maximum temperature, found that the Yangtze River Basin was dominated by a general cooling trend during the period 1960-1985, but a warming trend in 1986-2012 and that cold-related indices significantly decreased and warm-related indices significantly increased. The increased extreme warm temperature and decreased extreme cold temperature events at a regional scale strongly influence the natural environment (Overland et al, 2014;Yu et al, 2017). Therefore, a quantitative analysis and prediction of the trends and changes of extreme temperature in local scale is highly required.…”
Section: Introductionmentioning
confidence: 99%
“…Popova (2007) documented a negative relationship between the NAO and snow depth in northwest Russia because in mild winters precipitation is more likely to fall as rain. Other studies have analyzed the effects of the Arctic Oscillation (AO), which is broadly analogous to the NAO, and shown similar climatic relationships (e.g., Frey and Smith 2003;Yu et al 2017). Previous work has also revealed that variability in autumn Eurasian snow cover, Arctic sea ice extent, North Atlantic sea surface temperature, and regional atmospheric circulation anomalies can feed back onto the subsequent winter NAO/AO (e.g., Chen et al 2020;Cohen et al 2020;Henderson et al 2018;Kryjov 2015;Wu et al 2013).…”
Section: Circulation Pattern Acronymmentioning
confidence: 99%
“…It has also been linked to above average precipitation in the West Siberian Plains and the Kola Peninsula (Ionita 2014;Lim 2015). During the positive phase of the winter SCA most of Eurasia north of 408N is colder than normal (Liu et al 2014), with an increase in the frequency of extreme cold events (Yu et al 2017). Decreased precipitation occurs over northwestern Russia, the West Siberian Plains, and some of the Arctic coastal region, associated with reduced storm-track activity (Bueh and Nakamura 2007;Popova 2007;Liu et al 2014).…”
Section: Circulation Pattern Acronymmentioning
confidence: 99%
“…After data quality control and homogeneity, sixteen extreme indices (Table 1) were selected. These indices are widely used to evaluate the changes in climate extremes [22,[49][50][51]. The possible associations between the chosen indices and the ACPs were analyzed by a multiple regression method.…”
Section: Datamentioning
confidence: 99%